Some modern aspects of the pathogenesis of tuberculous infection in children - N. S. Kolisnyk (Patologìâ)
The article covers the modern pathogenetic mechanisms of development of tuberculous infection in children. An attempt to generalize present literary data about the features of cytikine status, role and maintenance of nitric oxide in different course of tuberculous infection was done, attention was paid to vegetative disorders and metabolic violations in tuberculosis. Further study of mechanisms of pathogenesis of tuberculosis is of interest with the purpose of including pathogenetic drugs into the treatment regimen for correction immune, metabolic, vegetative dysfunctions. tuberculous infection; children;immune responsiveness; cytokines, nitric oxide, vegetative nervous system